HUBUNGAN ANTARA POLA ASUH ORANG TUAÂ DENGAN MOTIVASI BERPRESTASI SISWA KELAS VIII DI SMP NEGERI 1 SANGKAPURA GRESIK - HERMAWAN EKO SUSANTO, AKIF (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract The correlation between parents and children will influence in children’s successfull. Usually parents have specification pattern of parenting to their children. If the parents apply effectively parenting, the children will grow up well and have positive change in their selves appropriate to their parent’s hope so their activities outside will not worry their parents. The parenting parent is one of the factors and important aspect that can support student’s behavior to get achievement. The parenting parent also influences to the student’s intellectual development, including the development of student’s achievement motivation. If the parenting parent can support the high achievement motivation, surely the student’s achievement also will be high. The aim of this research is to know the correlation between parenting parent with the achievement motivation of eighth grade students in SMP Negeri 1 Sangkapura Gresik. In this research, the researcher used the descriptive research. While the research design which is used is single correlation design. Population in this research is for 120 students. By using cluster random sampling so the research chose the group not the individual, so the number of 34 students of grade eight in class VIII care chosen. The data research was taken through parenting parent questionnaire and achievement motivation questionnaire. This research used the quantitative with correlation study and analysis data used coefficient contingency. Based on this research from the sample contains 34 students, the number of 33 students included in group of type parenting parent 3 with percentage of 97,05% with the detail the number students is five with most less achievement motivation, 5 students included in less achievement, 4 students included in middle achievement, 10 students included in high achievement and 9 students included in very achievement. While 1 students included in second parenting parent type that is 2,92% with higher categorize motivation. Then from the analysis coefficient contingency is got from the result of 0,244. So there is no significance correlation with the parenting parent with the achievement motivation of grade eighth students in SMP Negeri 1 Sangkapura Gresik with contribution of 0,0595% and the rest 99,94% is influenced by other factor. Keywords:  parenting parent, achievement motivation